PENGARUH KESADARAN PAJAK, SANKSI PAJAK, DAN KEPERCAYAAN PAJAK PADA PEMERINTAH TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Dwi Atmoko, Agus (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
The development of MSMEs in Indonesia has increased very rapidly every year. This can be seen from data from the Ministry of Cooperatives and SMEs in 2021, that the number of MSMEs in Indonesia reached 64.2 million with a contribution to GDP of 61.07% or Rp 8,573.89 trillion. MSMEs pay taxes to the state which is quite significant, but many MSME actors do not understand and are aware of their tax obligations. Therefore, the government needs to increase taxpayer compliance in various ways, This study aims to find out and analyze the influence of tax awareness, tax fines, and government tax trust on the level of taxpayer compliance in the tumpeng sewu MSME forum in Butuh district which amounted to 50 MSME actors. The number of administrators and members registered in the tumpeng sewu MSME forum as taxpayers was used for sampling as many as 50 people. The data analysis method used in testing the hypothesis of this study is multiple regression analysis. This sampling technique The results of this study show that tax awareness, tax sanctions, and tax trust in the government have a positive effect on the level of taxpayer compliance in the tumpeng sewu MSME forum in Butuh district. This is shown by a determination coefficient of 8,493 which means that tax awareness, tax sanctions, and tax trust in the government affect the level of taxpayer compliance by 849%. At the same time, tax awareness, tax sanctions, and tax trust in the government have